Navigating complex decision in a new setting; perspectives of Arabic-speaking migrant men in Sweden on family planning decision making - Mazen Baroudi; Elin C. Larsson; Helena Kilander (PLoS ONE, 2025)
Background Male partners’ involvement in family planning can be crucial for women’s contraceptive choices. Limited research exists on migrant men’s experiences and perceptions of family planning and associated decisions. The study aims to investigate experiences and perceptions of family planning use and decision-making among Arabic-speaking men living in Sweden. Methods This qualitative study utilized reflexive thematic analysis of eighteen in-depth interviews. The participants aged 22–43 years, had relocated to Sweden within the past decade, and represented various countries of origin (e.g., Syria, Iraq, Palestine) with most participants having 13 or more years of education. Results We identified an overarching theme, “Navigating the complex family planning decision-making in a new setting” supported by four sub-theme; 1) “The new living conditions influencing family planning decision-making” described how financial (in)stability, childcare responsibilities, personal development goals, and the impact of changing circumstances shaped family planning choices; 2) “Social norms affecting family planning decision-making” emphasized the diversity of gender roles and norms within Arabic-speaking communities, with an emphasis on joint decisions and shared responsibility. Instances of controlling behaviour and the role of beliefs and extended family members were also noted; 3) “Challenges in accessing contraceptive services free of discrimination” underscored the need for and importance of access to comprehensive information and culturally sensitive services in shaping family planning decisions; 4) “Conflicting considerations when deciding on contraceptive method” addressed factors such as familiarity with the methods, perceived effectiveness and safety, fear of side-effects, and taboos associated with the methods. Conclusions The findings highlight the diverse factors influencing family planning decisions. The study underscores men’s willingness to be active partners for family planning and highlights the need for improved information provision and services to empower informed decision-making.